Kv1.1 channelopathy abolishes presynaptic spike width modulation by subthreshold somatic depolarization - Vivekananda, Umesh (2017)
Although action potentials propagate along axons in an all-or-none manner, subthreshold membrane potential fluctuations at the soma affect neurotransmitter release from synaptic boutons. An important mechanism underlying analog-digital modulation is depolarization-mediated inactivation of presynaptic Kv1-family potassium channels, leading to action potential broadening and increased calcium influx. Previous studies have relied heavily on recordings from blebs formed after axon transection, which may exaggerate the passive propagation of somatic depolarization. We recorded instead from small boutons supplied by intact axons identified with scanning ion conductance microscopy in primary hippocampal cultures and asked how distinct potassium channels interact in determining the basal spike width and its modulation by subthreshold somatic depolarization. Pharmacological or genetic deletion of Kv1.1 broadened presynaptic spikes without preventing further prolongation by brief depolarizing somatic prepulses. A heterozygous mouse model of episodic ataxia type 1 harboring a dominant Kv1.1 mutation had a similar broadening effect on basal spike shape as deletion of Kv1.1; however, spike modulation by somatic prepulses was abolished. These results argue that the Kv1.1 subunit is not necessary for subthreshold modulation of spike width. However, a disease-associated mutant subunit prevents the interplay of analog and digital transmission, possibly by disrupting the normal stoichiometry of presynaptic potassium channels.